1998
DOI: 10.3354/meps166053
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic activity of natural microphytobenthos populations measured by fluorescence (PAM) and 14C-tracer methods:a comparison

Abstract: PAM (pulse-amplitude-modulated) fluorescence measurements of motile microphytobenthic algae were carried out in June 1996 at Sylt, Germany. Compansons between "C-based and fluorescence-based production rates were made. A very high correlation between 14C-and fluorescence-based production rates was found for maximal production rates (P, , values). I4C-based maximal production rates var~ed during the study penod between 0.65 and 1.7 mg C mg chl a-' h-', comparable to variations of P,,, measured with the fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 22 publications
3
92
1
Order By: Relevance
“…The differences between the 2 methods could also be caused by the fact that the medium was kept in motion by a stirrer as opposed to the 14C measurements (Hartig et al 1998 Gallagher (1990) proposed that the production of microalgae could be enhanced by stirring the overlying water over a sediment core. Also, H. Lindeboom in Colijn et al (1983) observed a 4.3 to 8.8 higher production measured with the oxygen method (microelectrodes) compared to the I4C technique.…”
Section: Application Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences between the 2 methods could also be caused by the fact that the medium was kept in motion by a stirrer as opposed to the 14C measurements (Hartig et al 1998 Gallagher (1990) proposed that the production of microalgae could be enhanced by stirring the overlying water over a sediment core. Also, H. Lindeboom in Colijn et al (1983) observed a 4.3 to 8.8 higher production measured with the oxygen method (microelectrodes) compared to the I4C technique.…”
Section: Application Of the Methodsmentioning
confidence: 99%
“…comm.). Additionally, the lens tissue technique had to be used during this study, because fluorescence induction kinetics of the microphytobenthos were measured at the same time by the pulse-amplitude modulated (PAM) fluorescence technique (Hartig et al 1998). Both methods, the Photosynthetic Light Dispensation System and the PAM technique, were developed for photosynthetic research of higher plants or phytoplankton (Dubinsky et al 1987, Edwards & Baker 1993, Schreiber & Bilger 1993 and were tested here for the first time for studies on microphytobenthic communities.…”
Section: Application Of the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ETR of algal suspensions is often linearly correlated to O 2 -production or C-fixation at limiting irradiances; however, sometimes at saturating irradiance, ETR can under-or overestimate the maximum rate of photosynthesis (Flameling & Kromkamp 1998, Hartig et al 1998, Masojídek et al 2001. Comparisons of ETR and standard measures for the quantification of undisturbed MPB biofilm photosynthetic rates are rare, and the published results are often contradictory (Barranguet & Kromkamp 2000, Perkins et al 2002, Serôdio 2003.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 98%
“…According to theory, using either 'multiple' or 'single' turnover saturation kinetics (see Kromkamp & Forster 2003) the effective quantum efficiency of Photosystem II (PSII) (ΔF/F m '), which generally represents the effective quantum efficiency of photosynthesis (Φ P ) (Genty et al 1989), can be derived at a range of irradiances. If ΔF/F m ' is then multiplied by the irradiance absorbed by PSII, the rate of non-cyclic electron transport (ETR) can be calculated (Hofstraat et al 1994, Kromkamp & Forster 2003, which can be converted to a photosynthetic rate by multiplying by the electron use efficiency (Φ e , mol C fixed per mol electrons produced by PSII) (Gilbert et al 2000).ETR of algal suspensions is often linearly correlated to O 2 -production or C-fixation at limiting irradiances; however, sometimes at saturating irradiance, ETR can under-or overestimate the maximum rate of photosynthesis (Flameling & Kromkamp 1998, Hartig et al 1998, Masojídek et al 2001. Comparisons of ETR and standard measures for the quantification of undisturbed MPB biofilm photosynthetic rates are rare, and the published results are often contradictory (Barranguet & Kromkamp 2000, Perkins et al 2002, Serôdio 2003.…”
mentioning
confidence: 99%